Student Collaboration In Maintenance Of Muslim Places Of Worship: A Case Study At Rajamangala University Of Technology Krungthep Thailand: Kolaborasi Mahasiswa dalam Pemeliharaan Tempat Ibadah Muslim: Studi Kasus di Universitas Teknologi Rajamangala Krungthep, Thailand - Amadea Syahbani Rachela Putri; Faiz Umar Hadi; Gerald Reyhan Gunswantana; Vania Amanda; Wiwik Handayani (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
This international community service aims to provide real support and contribution in the maintenance of the prayer room at Rajamangala University, Thailand. This community service activity is carried out by a cross-country team involving students, lecturers, and educators from various disciplines. The main focus of this community service is the maintenance of the physical facilities of the prayer room, such as repainting, repairing prayer facilities, and cleaning the surrounding environment. In addition, this program also seeks to strengthen relations between international Muslim communities and raise awareness of the importance of a decent place of worship as a center of spirituality in the campus environment. This community service is expected to have a positive impact on the comfort of Muslim students and staff in worship, as well as strengthening international cooperation in the social and cultural context.